The trellis and the vine : the ministry mind-shift that changes everything - Marshall, Colin, 1949-; Payne, Tony, 1962-; Matthias Media (Kingsford, N.S.W. : Matthias Media, 2009)
All Christian ministry is a mixture of trellis and vine. There is vine work: the prayerful preaching and teaching of the word of God to see people converted and grow to maturity as disciples of Christ. Vine work is the Great Commission. And there is trellis work: creating and maintaining the physical and organizational structures and programs that support vine work and its growth. Colin Marshall and Tony Payne dig back into the Bible's view of Christian ministry, and argue that a major mind-shift is required if we are to fulfill the Great Commission of Christ, and see the vine flourish again. --from publisher description
Accompanying DVD titled: Matthias Media resources for gospel growth : an introduction to the publishing ministry of Matthias Media
Includes bibliographical references
Keywords: Pastoral theology; Discipling (Christianity); Mission of the church